Achieving the 95 95 95 targets for all: A pathway to ending AIDS - Luisa Frescura; Peter Godfrey-Faussett; Ali Feizzadeh A.; Wafaa El-Sadr; Omar Syarif; Peter D. Ghys; on and behalf of the 2025 testing treatment target Working Group (PLoS ONE, 2022)
In December 2020, UNAIDS released a new set of ambitious targets calling for 95% of all people living with HIV to know their HIV status, 95% of all people with diagnosed HIV infection to receive sustained antiretroviral therapy, and 95% of all people receiving antiretroviral therapy to have viral suppression by 2025. Adopted by United Nations Member states in June 2021 as part of the new Political Declaration on HIV and AIDS, these targets, combined with ambitious primary prevention targets and focused attention to supporting enablers, aim to bridge inequalities in treatment coverage and outcomes and accelerate HIV incidence reductions by focusing on progress in all sub-populations, age groups and geographic settings. Here we summarise the evidence and decisions underpinning the new global targets.